Analisis Kesiapan Sekolah Terhadap Protokol Kesehatan Untuk Belajar Offline Sekolah Dasar Di Kota Pekanbaru - Anggi Wahyudi; Yefma Feby Handika (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In this era of the Covid-19 pandemic, it affects most of our lives, including the education sector.Currently, the government is intensively disseminating the policy of adapting new habits or new normal, which is defined as a change in normal community behavior activities by paying attention to health protocols in which there is a policy regarding face-to-face learning (offline). This study aims to provide an analysis from the author's point of view regarding the readiness of schools for the health protocol in facing face-to-face learning, especially elementary schools in Pekanbaru City. The research method used in analyzing school readiness for the health protocol in dealing with face-to-face learning is a quantitative descriptive method in which researchers collect data through filling out observation sheets and questionnaires addressed to principals and teachers in elementary schools in Pekanbaru City. With the number of samples in this study were 30 Elementary Schools. The results obtained from the assessment of the physical environment, non-physical and health protocols of 30 elementary schools. Physical environment that most of the schools meet the requirements with the highest percentage of (100%) for the 6 physical assessment indicators and 2 of them are (66.67% and 16.67%) respectively. The non-physical environment shows that of the three indicators, the percentages meet the requirements of (76.67% and 100%). As for the Health protocol of 6 criteria indicators that meet the requirements with a percentage above (50%) there are 7 indicators while the rest are below (50%) with the lowest percentage of (33.33%). in terms of the readiness of learning support facilities and infrastructure and health protocols, most schools are ready and able to conduct face-to-face learning (offline).